Altering distances and fixed point results for tangential hybrid pairs of mappings - Akkouchi, Mohamed; Popa, Valeriu (Annales Mathematicae Silesianae, 2013)
The aim of this paper is to prove a general fixed point result by altering distances for two occasionally weakly compatible (owc) pairs of hybrid mappings and to reduce the study of fixed points of the pairs of mappings satisfying a contractive condition of integral type at the study of fixed points in metric spaces by altering distances satisfying a new type of implicit relations generalizing the result recently obtained by H.K. Pathak and Naseer Shahzad (see Bull. Belg. Math. Soc. Simon Stevin, 16 (2009), 1-12) which is of Gregus type.